Analysis of the Influence of Capital Intensity, Inventory Turnover (ITO) and Return on Assets (RoA) on the Effective Tax Rate (Etr) with Institutional Ownership as a Moderating Variable - Nur Azizah Mariani (Publikasi Indonesia, 2024)
The aim of this research is to determine the effect of capital intensity, inventory turnover (ITO), and return on assets (ROA) on the effective tax rate (ETR) with institutional ownership as a moderating variable. This research uses secondary data in the form of financial reports that have been audited by auditors, where the data was obtained from the official website of the Indonesia Stock Exchange (IDX) at idx.co.id. The sampling technique used in this research is the purposive sampling method. The population in this research is property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021, totaling 9 companies. The sample used in this research was 41 companies with 123 observation data, taken based on certain criteria. This research is quantitative research with secondary data sources including the company's annual financial reports obtained through the website www.idx.co.id and the official website of each company. The method used to analyze the influence of independent variables on the dependent variable in this research is multiple linear regression analysis using SPSS 26. The results of the research show that Return on Assets and Inventory Turnover (ITO) have a positive and significant effect on the Effective Tax Rate, while Capital Intensity has a negative effect. but it is not significant to the Effective Tax Rate for property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Institutional ownership can moderate the influence of Capital Intensity, Return on Assets, and Inventory Turnover (ITO) on the Effective Tax Rate in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX).